PENGARUH PENDIDIKAN DAN LATIHAN (DIKLAT) TERHADAP KINERJA GURU DI SMP NEGERI 1 KECAMATAN SUNGGAL KABUPATEN DELI SERDANG (PIONIR: JURNAL PENDIDIKAN, 2022)
The purpose of this study was to determine how much influence education and training had on teacher performance at SMP Negeri 1 Sunggal. This type of research was quantitative with the total population in this study was 43 people. The method used in sampling in this study is total sampling. The data collection method used a questionnaire, the data analysis method used description analysis, requirements analysis test, and hypothesis testing. The results of this study stated that the distribution of Education and Training scores (X) was 13 people (30.2%) below the interval class average, 14 people (32.6%) were in the interval class average and 16 people ( 37.2%) above the average. This condition illustrates that the education and training at SMP Negeri 1 Sunggal based on the data above is above the interval class average. This shows that the training carried out at SMP Negeri 1 Sunggal shows an increase in teacher performance. The distribution of Teacher Performance scores (Y) as many as 29 people (67.5%) is below the interval class average, 11 people (25, 6%) were in the average class interval and as many as 3 people (7%) were above the average. Based on the data above, it can be seen that in general the teacher's performance is above the average. There is a positive influence between the training variables on teacher performance at SMP Negeri 1 Sunggal seen by the regression line equation = 138,089+0.724X with a constant of 138,089 stating that if there is no training value, the teacher's performance value is 138,089. While the regression coefficient X of 0.724 means that for every addition of 1 teacher performance value, the value of education and training increases by 0.724 or 72.4%. and the significance can be seen through the t-test obtained tcount of 3.317 while the value of ttable with a value of N = 43, then the significance of 0.05 is 2.01954. Therefore, tcount (3.317) > ttable (2.01954) with a significance level of 0.003
Keywords: Training; Teacher Performance